2014
DOI: 10.1155/2014/141360
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Prognostic Relevance ofFLT3Mutations in Saudi Acute Myeloid Leukemia Patients

Abstract: The Fms-like tyrosine kinase-3 (FLT3) is a receptor tyrosine kinase that plays a key role in cell survival, proliferation, and differentiation of hematopoietic stem cells. Mutations of FLT3 were first described in 1997 and account for the most frequent molecular mutations in acute myeloid leukemia (AML). AML patients with FLT3 internal tandem duplication (ITD) mutations have poor cure rates the prognostic significance of point mutations; tyrosine kinase domain (TKD) is still unclear. We analyzed the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
3
7
1
Order By: Relevance
“…On the other hand, the results revealed significant higher leukocytosis in patients with FLT3-ITD (p= 0.023) and higher blast percentage (p=0.008) compared to patients with wild-type FLT3. These findings are in accordance to previously reported (Kottaridis et al, 2001;Frohling et al, 2002;Wang et al, 2010;Su et al, 2013;Elyamany et al, 2014) but in disagreement with that reported by Shahab et al (2013).…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, the results revealed significant higher leukocytosis in patients with FLT3-ITD (p= 0.023) and higher blast percentage (p=0.008) compared to patients with wild-type FLT3. These findings are in accordance to previously reported (Kottaridis et al, 2001;Frohling et al, 2002;Wang et al, 2010;Su et al, 2013;Elyamany et al, 2014) but in disagreement with that reported by Shahab et al (2013).…”
Section: Discussionsupporting
confidence: 66%
“…In our study the frequency of FLT3-ITD mutation was 18.5%. Elyamany G et al14 have reported a frequency of 14.4% in the Saudi AML patients. FLT3-ITD mutations were found in 19.2% of the AML patients in Thailand by Kumsaen P et al15 However, both the studies by Elmany G et al14 and Kumsaen P et al15 have included both the paediatric and adult population while we have only studied these mutations in adults.…”
Section: Discussionmentioning
confidence: 96%
“…Blast cell count and CD34 expression had significant association with the FLT3-ITD gene mutation in AML. Some studies have also reported that the presence of FLT3-ITD gene mutation is significantly associated with the higher blast cell count and CD34 expression (7,17,18,24). Normal FLT3 and negative expression of CD34 predict a longer survival (25).…”
Section: Discussionmentioning
confidence: 99%